The MPM-2 antibody inhibits mitogen-activated protein kinase activity by binding to an epitope containing phosphothreonine-183. - Taagepera, S (1994)
Mitogen-activated protein (MAP) kinases are a family of serine/threonine kinases implicated in the control of cell proliferation and differentiation. We have found that activated p42mapk is a target for the phosphoepitope antibody MPM-2, a monoclonal antibody that recognizes a cell cycle-regulated phosphoepitope. We have determined that the MPM-2 antibody recognizes the regulatory region of p42mapk. Binding of the MPM-2 antibody to active p42mapk in vitro results in a decrease in p42mapk enzymatic activity. The MPM-2 phosphoepitope can be generated in vitro on bacterially expressed p42mapk by phosphorylation with either isoform of MAP kinase kinase (MKK), MKK1, or MKK2. Analysis of p42mapk proteins mutated in their regulatory sites shows that phosphorylated Thr-183 is essential for the binding of the MPM-2 antibody. MPM-2 binding to Thr-183 is affected by the amino acid present in the other regulatory site, Tyr-185. Substitution of Tyr-185 with phenylalanine results in strong binding of the MPM-2 antibody, whereas substitution with glutamic acid substantially diminishes MPM-2 antibody binding. The MPM-2 phosphoepitope antibody recognizes an amino acid domain incorporating the regulatory phosphothreonine on activated p42mapk in eggs during meiosis and in mammalian cultured cells during the G0 to G1 transition.